2019
DOI: 10.1186/s12913-019-4641-9
|View full text |Cite
|
Sign up to set email alerts
|

E-learning as valuable caregivers’ support for people with dementia – A systematic review

Abstract: BackgroundPresent demographic trends show a considerable rise in elderly populations with aging disorders, such as dementia. The current article focused on the exploitation of e-learning as an informal support for caregivers of people with dementia and considered its benefits and limitations to provide proper and relevant care for this target group of people as well as maintain the quality of life of their caregivers.MethodsThe methodology of this study is based on a literature review of accessible peer-review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 43 publications
0
29
0
4
Order By: Relevance
“…A systematic meta-review of interventions targeting self-management of ICs of PWD found that such interventions can improve their stress levels, social support, and quality of life ( Verkaik et al., 2015 ). Another systematic review specifically examined the delivery modality of Internet-based remote self-management education and peer support for informal caregivers of individuals with dementia and found it can help reduce informal caregivers’ stress levels and improve feelings of support ( Klimova et al., 2019 ). Given the efficacy of interventions designed to improve the health and well-being of ICs of PWD, better understanding how the pandemic has impacted such caregivers can inform future interventions to address stress and health problems stemming from caregiving through the pandemic along with the everyday issues normally encountered.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic meta-review of interventions targeting self-management of ICs of PWD found that such interventions can improve their stress levels, social support, and quality of life ( Verkaik et al., 2015 ). Another systematic review specifically examined the delivery modality of Internet-based remote self-management education and peer support for informal caregivers of individuals with dementia and found it can help reduce informal caregivers’ stress levels and improve feelings of support ( Klimova et al., 2019 ). Given the efficacy of interventions designed to improve the health and well-being of ICs of PWD, better understanding how the pandemic has impacted such caregivers can inform future interventions to address stress and health problems stemming from caregiving through the pandemic along with the everyday issues normally encountered.…”
Section: Introductionmentioning
confidence: 99%
“…There are many forms of internet-based activities that can meet the caregiver’s needs such as web-based training, psychological and educational programs, mobile text messaging, video-recording, and chat forums [ 14 ]. Furthermore, dementia technology based on the internet (e.g., smartphone apps, wearables, computer programs, e-learning, and online platforms) can support care and improve contact with professional care personnel, enhancing the monitoring of disease progression, identifying emerging problems, and delivering professional interventions [ 15 , 16 ], which could be a cost-effective solution in the long-term. In a pilot study, Boessen et al identified the family caregivers’ requirements and determined the need for reliable information regarding the disease and contact with fellow family members to be crucial [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that blended learning imposed a positive effect on the attitude of the caregivers of cancer patients under chemotherapy. Klimova et al (2019) evaluated the impact of electronic learning on the caregivers of patients with dementia. The results revealed that electronic training courses helped the caregivers to have a better self-con dent, sympathy, understanding, and ability (P < 0.03) (25).…”
Section: Impact Of Blended Learning On Attitudementioning
confidence: 99%